Pengaruh Pembayaran Non Tunai (QRIS), Literasi Keuangan, dan Penerapan Manajemen Keuangan Terhadap Kinerja UMKM (Jalan Gatot Subroto Kecamatan Serengan Surakarta) - Rizal Rohmad Evendi; Setyaningsih Sri Utami (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyse the impact of cashless payments (Quick Response Code Indonesian Standard or QRIS), financial literacy, and the implementation of financial management on the performance of Micro, Small and Medium Enterprises (MSMEs) located on Jalan Gatot Subroto, Serengan District, Surakarta. The research approach employed is a quantitative method utilising primary data sources. The population in this study comprises 300 MSME units in the area, with the sample determined using cluster random sampling. Based on calculations using the Slovin formula, a sample of 75 respondents was determined. Data were collected through the distribution of questionnaires and analysed using a series of statistical procedures, including descriptive analysis, multiple linear regression, t-tests, F-tests, and analysis of the coefficient of determination (R²). The results of instrument testing via validity and reliability tests confirmed that all items within the variables of cashless payments, financial literacy, and financial management were valid and reliable. Furthermore, the research model met the requirements of classical assumption tests, which included tests for normality, multicollinearity, and heteroscedasticity. The research findings indicate, in part, that: (1) non-cash payments have a significant effect on MSME performance, (2) financial literacy has a significant effect on MSME performance, and (3) the implementation of financial management has a significant effect on MSME performance.